Incremental reflexion analysis. Issue 6 (28th June 2011) - Koschke, Rainer; Capilla, Rafael; Dueñas, Juan C.; Ferenc, Rudolf
SUMMARY Architecture conformance checking is implemented in many commercial and research tools. These tools typically implement the reflexion analysis originally proposed by Murphy, Notkin, and Sullivan. This analysis allows for structural validation of an architecture model against a source model connected by a mapping from source entities onto architecture entities. Given this mapping, the reflexion analysis computes the discrepancies between the architecture model and source model automatically. The mapping process is usually highly interactive and the most time‐consuming activity in the reflexion analysis. In current tools, the reflexion analysis must be repeated completely whenever the underlying source or architecture models or the mapping changes. In large systems, the recomputation can hinder interactive use as users expect an immediate response to their changes. This paper describes an incremental reflexion analysis that does not require a complete repetition of the reflexion analysis. Instead, it repeats the analysis only for those parts that are actually influenced by a change. The incremental reflexion analysis is evaluated on large real‐world systems. Copyright © 2011 John Wiley & Sons, Ltd.